Modelling of turbidity water plume at estuaries - Ninh, Pham Van; Duc, Bui Minh; Vinh, Phan Ngoc (Vietnam Journal of Mechanics, 1995)
In the paper results of numerical simulation of turbidity water plume based on the Random Walk technics are presented. A software which allows to describe the boundary and distribution of contaminant concentration of a plume with river and contaminant discharge, tide and wind currents and complicated topography of the basin taken into account, has been developed. The carried out numerical model has been verified well by remote sensing images for classification of the turbidity distribution of Red. Han and Me Kong estuaries. Some remarks have been made for using of the numerical model.